2023 Indonesian Guidelines for Heart Failure Treatment: Working Group on Heart Failure and Cardiometabolic Diseases, Indonesian Heart Association - Dian Yaniarti Hasanah, MD; Edrian - Zulkarnain, MD; Habibie - Arifianto, MD; Hawani Sasmaya Prameswari, MD; Leonardo Paskah Suciadi, MD; Paskariatne Probo Dewi Yamin, MD; Rarsari Soerarso Pratikno, MD; Siti Elkana Nauli, MD; Vebiona Kartini Prima Putri, MD; Wahyu Aditya Soedarsono, MD; Yuke - Sarastri, MD (Majalah Kardiologi Indonesia)
Heart failure is a health problem with high mortality and morbidity rates in developed and developing countries such as Indonesia. The prevalence of heart failure itself is increasing because patients who experience acute heart failure can progress to chronic heart failure. Guidelines-Directed Medical Therapy (GDMT) with recommended doses is still underutilized in heart failure patients with reduced ejection fraction (HFrEF). In Indonesia itself, even though it has a fairly high rate of use of ACE-inhibitors (ACE-I) or angiotensin receptor blockers (ARB), Indonesia has the lowest rate of use of β-blockers and aldosterone inhibitors (also called Mineralocorticoid Receptor Antagonists, MRA) of the entire ASIAN-HF registry.84